WARUNKI SYNOPTYCZNE PODCZAS WYSTĘPOWANIA WYSOKICH KONCENTRACJI PM10 W POZNANIU W LATACH 2010–2017 - Kendzierski, Sebastian; Forycka–Ławniczak, Hanna (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2025)
The article presents examples of synoptic situations when the permissible concentration of PM10 was severely exceeded in 2010–2017 in Poznań. In many Polish cities, there are deviations from the norms for a number of days during the year. The scale of concentration of PM10 in the air is largely affected by the prevailing meteorological conditions such as low temperature and low wind speed. First, periods of the highest daily concentrations of pollutants were selected. Subsequently, synoptic maps for selected days were analysed. The most common cause of the pollution was a large boom which brought Arctic air to Poland. In this case, the highest concentration was accompanied by very low air temperatures and the resulting more intensive heating of buildings.